Perilaku Bullying Terhadap Kepercayaan Diri Siswa - Tadhawwara Puji Astuti; Haning Tri Widiastuti (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2024)
Bullying behavior is a problem in this research. With cases of bullying behavior carried out by students against their own friends, such as physical, verbal, cyberbullying and relational bullying. This research was conducted with the aim of finding out whether there is an influence of bullying behavior on students' self-confidence at SMAN 3 Depok. This research uses associative quantitative which looks at the influence between variables X and Y. The sampling technique used was simple random sampling, totaling 260 people. The research results showed "there is no positive and significant influence between bullying behavior and the self-confidence of students at SMAN 3 Depok" as seen from the Fcount < Ftable value, namely 1.847 < 3.86. So, it can be interpreted that Ho, who states that bullying behavior has no positive effect on students' self-confidence, and Ha's consequences are rejected. The variable bullying behavior on self-confidence is 19%, while the rest is influenced by other variables not included in this research. Keywords: Bullying behavior, self-confidence.